Structural features of dioxane lignin from Eucalyptus globulus and their relationship with the pulp yield of contrasting genotypes - Graciela Aguayo, María; Ruiz, José; Norambuena, Marcela; Teixeira Mendonça, Regis (Maderas. Ciencia y Tecnología, 2025)
The chemical structure of dioxane lignins isolated from two groups of Eucalyptus globulus genotypes with contrasting pulpwood characteristics were evaluated. Six genotypes were selected and separated in two groups (G1 and G2) based on differences in wood density, pulp yield and chemical characteristics. Lignin was isolated from both milled wood and kraft pulps produced at kappa number 16, and were characterized by different techniques such as FTIR, elemental analysis, molar mass distribution and 31P NMR spectroscopy. From the different characteristics evaluated, some were determined as more relevant, such as syringyl (S) and guaiacyl (G) amounts, S/G ratio and condensed biphenyl units, were correlated with the pulp yield. High correlations were found between pulp yield and syringyl units (R2 = 0,69), and pulp yield and syringyl/guaicyl ratio (R2 = 0,88). The condensed 5-5 biphenyl units presented a negative correlation with pulp yield (R2 = 0,76). The information obtained explained part of the difference in pulpability of the contrasting genotypes and can be used for the selection and improvement of the species for the pulp and paper industry.